Peningkatan gerak dasar melalui permainan kasti - Syayyif Al-Fathi, Zamahsyari; Maksum, Ali; Yuli Hartati, Sasminta Christina; Kristiyandaru, Advendi; Diaztiarni, Diaztiarni; Sumarsono, Agus (Jurnal Porkes, 2024)
The purpose of this study was to improve the quality of learning in the classroom, especially the basic movements of students by using a baseball game. This study uses classroom action research methodology. The population of this study was the entire fifth grade of SDN Ketintang 1 Surabaya as many as 26 people. The sample used cluster random sampling. This study will take 3 data needed by researchers, cognitive, affective, and psychomotor domains. The results of cycle 1 show the average value of both cognitive, affective, and psychomotor with varying average values. The average cognitive pretest 50 and posttest 80, there is a significant increase after being given treatment with a good predicate. For affective obtained an average score of 80 with a good predicate. The average student psychomotor 76 with a very good category but there are some students who still have not reached the minimum criteria of the assessment. Cycle 2 obtained an average in the pretest and posttest cognitive domain of 76 and 83, and for the affective domain obtained an average score of 85. For the psychomotor domain obtained an average score of 87. So that with the completion of a significant increase in the items and also the completeness carried out by students, it can be concluded that increasing students' basic movements through the inscription game can successfully improve students' knowledge, students' attitudes, and students' basic movements.